Analisis Efisiensi, Efektivitas dan Kontribusi Penerimaan Parkir Terhadap Penerimaan Pajak Daerah dan Retribusi Daerah Di Kabupaten Tanah Laut - Ridhoni, Fitri; Saleh, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to compare the efficiency, effectiveness, and contribution of parking revenue to the local tax revenue and levies of Tanah Laut Regency. This study uses quantitative descriptive methods. The data type used is data from the secretariat data collection techniques by documentation from the Tanah Laut Regency Regional Revenue Agency. The results of this study show the efficient rate of parking revenue for Tanah Laut Regency in 2017-2021 for an average parking tax of 20,54%, the levy on parking service at the edge of the road public transportation is 25,03%, parking special space levy is 25,66%. The effectiveness of Tanah Laut Regency parking revenue for parking tax is an average of 106,259%, the levy on public road parking services is 133,146%, and the parking special space levy is 115,547%. The contribution rate of parking tax to local tax revenue in Tanah Laut Regency has an average of 0,0321%. The contribution rate of the parking levy to the revenue of the local levies of Tanah Laut Regency for parking service levies on public roads is 0,37%, and 4,088% is for levies on special parking spaces.